PENERAPAN SISTEM PENDUKUNG KEPUTUSAN TERHADAP PENENTUAN PEMINATAN PADA PROGRAM STUDI TEKNIK INFORMATIKA MENGGUNAKAN METODE ARAS - Yuyun Dwi Lestari; Arief Budiman; Dedy Irwan (Politeknik Bisnis Indonesia, 2023)
The selection of specialization is carried out by students of the Informatics Engineering study program while still in semester 5, namely Multimedia & Computer Vision, Network & Computer Systems, Robotics & Intelligent Systems. The selection of this specialization is carried out by students so that students focus on 1 specialization only and this specialization is carried out based on elective courses, so that students are not wrong in choosing their interests and do not follow the interests chosen by their friends. The purpose of this study is as an alternative to support students to determine the specialization in accordance with the criteria and calculate the value of each criterion to choose an interest and make a decision support for the selection of specialization to help students choose the right specialization according to the criteria quickly and precisely. Therefore, in the selection of student specialization in the Informatics Engineering study program requires a Decision Support System by applying the ARAS method. The results obtained from this study are the specialization of Network & Computer Systems in rank 1 with a value of 0.83554. Multimedia & Computer Vision ranked 2nd with a value of 0.78358. Robotics & Intelligent Systems ranked 3rd with a value of 0.77223. So that the specialization of Network & Computer Systems will be an alternative.